Do surgical emergencies stay at home? Observations from the first United States Coronavirus epicenter. Issue 1 (July 2021) - Dong, Caroline T.; Liveris, Anna; Lewis, Erin R.; Mascharak, Smita; Chao, Edward; Reddy, Srinivas H.; Teperman, Sheldon H.; McNelis, John; Stone, Melvin E.
Abstract : BACKGROUND: During the coronavirus disease 2019 pandemic, New York instituted a statewide stay-at-home mandate to lower viral transmission. While public health guidelines advised continued provision of timely care for patients, disruption of safety-net health care and public fear have been proposed to be related to indirect deaths because of delays in presentation. We hypothesized that admissions for emergency general surgery (EGS) diagnoses would decrease during the pandemic and that mortality for these patients would increase. METHODS: A multicenter observational study comparing EGS admissions from January to May 2020 to 2018 and 2019 across 11 NYC hospitals in the largest public health care system in the United States was performed. Emergency general surgery diagnoses were defined using International Classification Diseases, Tenth Revision, codes and grouped into seven common diagnosis categories: appendicitis, cholecystitis, small/large bowel, peptic ulcer disease, groin hernia, ventral hernia, and necrotizing soft tissue infection. Baseline demographics were compared including age, race/ethnicity, and payor status. Outcomes included coronavirus disease (COVID) status and mortality. RESULTS: A total of 1, 376 patients were admitted for EGS diagnoses from January to May 2020, a decrease compared with both 2018 (1, 789) and 2019 (1, 668) ( p < 0.0001). This drop was most notable after the stay-at-home mandate (March 22, 2020; week 12). From March to May 2020, 3.3%, 19.2%, and 6.0% of EGS admissions were incidentally COVID positive, respectively. Mortality increased in March to May 2020 compared with 2019 (2.2% vs. 0.7%); this difference was statistically significant between April 2020 and April 2019 (4.1% vs. 0.9%, p = 0.045). CONCLUSION: Supporting our hypothesis, the coronavirus disease 2019 pandemic and subsequent stay-at-home mandate resulted in decreased EGS admissions between March and May 2020 compared with prior years. During this time, there was also a statistically significant increase in mortality, which peaked at the height of COVID infection rates in our population. LEVEL OF EVIDENCE: Epidemiological, level IV. Abstract : Supplemental digital content is available in the text.